Peranan Teknologi Pendidikan Dalam Mendukung Kinerja Dosen Pendidikan Teknik Bangunan Universitas Negeri Manado - Kembuan, Djubir R.E. (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the role of educational technology in supporting lecturers' performance and its contribution to student learning outcomes in the Building Engineering Education Study Program at Manado State University. The research design uses a sequential explanatory approach, starting with a quantitative stage through a survey of 20 lecturers and 100 students, followed by a qualitative stage through interviews, observations, and documentation studies. The research instruments include a Likert-scale questionnaire, interview guidelines, and classroom observations. Data analysis was carried out using descriptive statistics, Pearson correlation, multiple linear regression, and thematic analysis. The results showed that the level of educational technology utilization was in the high category (M = 119.77; SD = 7.11) and lecturer performance was also high (M = 119.13; SD = 7.13). There was a significant positive correlation between educational technology and lecturer performance (r = 0.317; p < 0.01), as well as a direct effect on student achievement (β = 0.189; t = 2.826) and mediating variables such as commitment (β = 0.366; t = 4.038) and learning independence (β = 0.211; t = 2.130). These findings reinforce the theories of Technological Pedagogical Content Knowledge (TPACK) and Task-Technology Fit (TTF), which emphasize the alignment between technology, pedagogy, and content as the foundation for increasing learning effectiveness. The study recommends strengthening lecturers' digital literacy, integrating technology into lesson planning, providing adequate infrastructure, and periodically evaluating the use of educational technology.